Carbon Emission Risk and Firms’ ESG Rating: Evidence from a Quasi-natural Experiment based on the Paris Agreement - Lu, Shiyu; Li, Zixin; Cheng, Bo (Journal of Environmental Accounting and Management, 2026)
Based on a quasi-natural experimental event that China signed the Paris Agreement in 2016, this paper uses a difference-in-difference (DID) model to systematically investigate the impact of rising carbon emission risk on firms’ ESG rating and its mechanism. The results show the signing of the Paris Agreement significantly improves the ESG level of firms with high-carbon emission risk. Moreover, this positive effect occurs by increasing the level of corporate green innovation and the attention of analysts. Further heterogeneity analysis suggests that the policy effect is stronger for high-carbon emission firms that are non-state owned, media focused, and low market competition.